2001
DOI: 10.1115/1.1387026
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Stress Induced Cavitation in a Journal Bearing With Axial Throughput

Abstract: The problem of predicting flow between rotating eccentric cylinders with axial throughput is studied. The system models a device used to test the stability of emulsions against changes in drop size distribution. The analysis looks for the major variation in flow properties which could put an emulsion at risk due to coalescence or breakage and finds the most likely candidate in the pressure gradient defined as the ratio of the difference between the maximum and minimum pressure to the arc length between the dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Examples of stress-induced cavitation in extensional flow and shear flow were discussed by Joseph (1998). Pereira, McGrath & Joseph (2001) did a theoretical study of cavitation in a journal bearing with axial throughput. They found that the inception of cavitation in a moving fluid is always stress-induced.…”
Section: Introductionmentioning
confidence: 99%
“…Examples of stress-induced cavitation in extensional flow and shear flow were discussed by Joseph (1998). Pereira, McGrath & Joseph (2001) did a theoretical study of cavitation in a journal bearing with axial throughput. They found that the inception of cavitation in a moving fluid is always stress-induced.…”
Section: Introductionmentioning
confidence: 99%
“…Cavitation could occur in polymer processing and lubrication applications where it has not been previously considered. In fact, Pereira et al15 demonstrated the effect of a PNSCC on cavitation in a journal bearing with axial throughput. A better understanding of the cavitation inception criterion will improve efforts at inhibiting cavitation when it is not desired, or ensuring cavitation when it is desirable.…”
Section: Introductionmentioning
confidence: 99%
“…[3], [4], [5], [13], and [14]. They are a set of sufficient conditions to provide a unique solution for the system performance: the pressure distributions P 1 = P 2 = P 3 , P 4 and the flow distributions…”
Section: Analysis Of Multiple-channel Grease Lubricationmentioning
confidence: 99%